Expatriate Failure in the Indian Information Technology Industry - A. N., Raghavendra; G., Nijaguna (Prabandhan: Indian Journal of Management, 2015)
The competitive business environment of the present century has made internationalization a growing strategic option for organizations that want to create and sustain competitive advantage. Globalization largely affects corporate culture and the employees therein. Specific to global organizations attempting to develop dynamic capabilities through expatriation of managers is the identification and selection of an adequate number of qualified managers with a strong desire or interest in managing subsidiaries. Any failure on the part of the expatriates leads to the decline in productivity of the firm. This study examines the relationship of expatriate turnover in the information technology industry by considering eight important variables, that is, lack of technical and managerial competencies, mutual trust and co-operation among co-workers, position of expatriates, perceived lack of support in their career plan, inability of the spouse to adjust to the new culture, other family related issues, inability of the expatriate to cope with large assignments, and manager's personality of 43 expatriates from 11 different multinational corporations. The study also investigated the relationship between the mentioned variables through hypotheses testing. Testing the hypotheses based on independent samples t - test, our results suggest that expatriate failure is significantly related to the lack of technical and managerial competencies, managerial position of expatriates, perceived lack of support in their career plan, and inability of the spouse to adjust to the new culture.